Pengenalan dan pengendalian hama jeruk siam di Desa Tanjung Kecamatan Koto Kampar Hulu Kabupaten Kampar - Hafiz Fauzana; Rusli Rustam; Nelvia Nelvia; Yetti Elfina; Muhammad Ali (Unri Conference Series: Community Engagement, 2019)
Citrus plants are one of the mainstay horticultural commodities in Kampar Regency, Riau Province, especially in Tanjung Village, Koto, Kampar Hulu District. The main obstacle to citrus cultivation is the large number of pest attacks. In the previous experience of citrus plants in Kampar Regency these plants had to be destroyed because theye were attacked by CVPD and Phythopthora spp. This service aims to provide knowledge to farmers in Tanjung Village about the types of pest that attack oranges, attack symptoms, influencing factors and control methods. The ultimate goal is to increase citrus production so that farmers' income increases. Dedication is given by counseling and demonstration methods. Results and achievements the service program resulted in improved farmers' knowledge and skills about the types of pest and environmentally friendly control techniques for citrus plants. The service method includes counseling and demonstration in service activities were very well responded by citrus farmers. Previously farmers had never received material on introduction and control of citrus pests, in addition they faced issues in citrus cultivation i.e. pest therefore e participants paid close attention and asked many questions. Evaluate the achievement of the results of the questionnaire by holding counseling about citrus pests, farmers became aware of types of citrus pest, attack symptoms, and alternative control techniques that are carried out since citrus farmers only had knowledge on and applied control techniques using synthetic pesticides. Thus this service provides great benefits to citrus farmers in controlling their citrus pests.